Oclusão em prótese sobre implante - parte I - Costa, Patrícia dos Santos; Gomes, Erica Alves; Pereira, Cassiano Costa Silva; Gaetti-Jardim, Ellen Cristina; Zuim, Paulo Renato Junqueira [UNESP]; Assunção, Wirley Gonçalves [UNESP]; Garcia Júnior, Idelmo Rangel [UNESP] (My University, 2011)
Osseointegrated implants have specific nature distinguish them from natural teeth making them more susceptible to the efforts generated by mastication. The absence of periodontal ligament, which absorbs the masticatory forces and allows the movement of the teeth interfere with the reception of occlusal loads and therefore the predictability of implants. In the boneimplant interface did not occur the phenomena of dissipation of impact, even the movement induced. Thus, during planning and installation of implant prosthesis, the type and characteristics of occlusal pattern adopted should be established with criteria to be no grounds for future failures. In this regard we highlight the occlusal overload generated by several reasons like the presence of premature contacts, interference during motion excursive, deleterious habits and inappropriate extensions on cantilevers. Thus, the objective is to provide a review of the literature regarding the importance of occlusion in oral rehabilitation with implants. Factors to be considered in establishing a favorable occlusion, consistent with prostheses on implants will be described

Os implantes osseointegrados apresentam natureza específica que os diferem dos dentes naturais tornandoos mais susceptíveis aos esforços gerados pela mastigação. A ausência do ligamento periodontal, que absorve as forças mastigatórias e permite a movimentação dos dentes, interferem na recepção de cargas oclusais e consequentemente na previsibilidade dos implantes. Na interface osso-implante não ocorrem os fenômenos de dissipação de impacto, nem mesmo a movimentação induzida. Assim, durante o planejamento e instalação de próteses implantossuportadas, o tipo e características do padrão oclusal adotado devem ser estabelecidos com critério para não serem motivos de falhas futuras. Nesse aspecto destacase a sobrecarga oclusal, gerada por motivos diversos como a presença de contatos prematuros, interferências durante movimentos excursivos, hábitos parafuncionais e extensões em cantilévers inadequadas. Desta forma, o objetivo deste trabalho é apresentar uma revisão de literatura abordando a importância da oclusão em reabilitações orais com implantes. Os fatores a serem considerados no estabelecimento de uma oclusão favorável, condizente às próteses sobre implantes, também serão descritos.
Keywords: Dental occlusion; Dental prosthesis; Dental implants; Oclusão dentária; Prótese dentária; Implantes dentários